The pivotal role of the private sector in achieving transport policy objectives - NIJKAMP, Peter; RIENSTRA, Sytze A. (European Spatial Research and Policy, 1998)
In the past few decades, devolution trends seem to dominate societal developments and government policies. The private sector's influence is increasing everywhere, also in the transport sector. However, transport measures are politically sensitive, while specific socio-economic features make transport provision sometimes not very attractive for the private sector. At the same time, the external costs of the transport sector are increasing, despite official public policies. To analyse how this may change, a private sector scenario is constructed, showing which problems may be solved when private sector involvement is largely increased and when government intervenes only by means of market-based measures. In such a scenario equity issues will receive much less attention and the transport system may become entirely different from what current policies aim at; in this scenario, collective transport modes will probably largely disappear (except air-planes); at the same time new - low emission - fuels will dominate the transport scene. In this private sector scenario environmental problems as well as congestion will largely be solved. It can be concluded that when governments are prepared to accept the loss of influence in a strategic sector and the society in general is prepared to accept less equity, increasing private involvement in the transport sector may help significantly in solving transport problems.